2002
DOI: 10.1539/joh.44.166
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Long‐Term Compliance with Drug Treatment for Hypercholesterolemia in Japanese Male Workers: I. Acceptability of Drug Treatment

Abstract: Acceptability and Long‐Term Compliance with Drug Treatment for Hypercholesterolemia in Japanese Male Workers: 1. Acceptability of Drug Treatment: Masayuki Tatemichi, et al. Department of Environmental and Occupational Health, Toho University School of Medicine—We performed a prospective study to assess the acceptability and long‐ term compliance with drug treatment for hypercholesterolemia in Japanese male workers aged 40 to 57 yr with hypercholesterolemia detected in legally required periodical physical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Furthermore, even when occupational health practitioners do provide advice to employees with hyperlipidemia, those employees are not inclined to receive such treatment. Tatemichi et al reported that when health experts advised employees at large workplaces who were found to require treatment for hypercholesterolemia to start drug therapy following a lack of response to three-month dietary therapy, approximately 50% agreed to receive drug therapy, while one-third of those who did not agree to receive drug therapy also rejected dietary therapy [19]. This was likely because employees with hypercholesterolemia have fewer subjective symptoms than those with other diseases and are unlikely to exhibit presenteeism despite poorly controlled cholesterol levels [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even when occupational health practitioners do provide advice to employees with hyperlipidemia, those employees are not inclined to receive such treatment. Tatemichi et al reported that when health experts advised employees at large workplaces who were found to require treatment for hypercholesterolemia to start drug therapy following a lack of response to three-month dietary therapy, approximately 50% agreed to receive drug therapy, while one-third of those who did not agree to receive drug therapy also rejected dietary therapy [19]. This was likely because employees with hypercholesterolemia have fewer subjective symptoms than those with other diseases and are unlikely to exhibit presenteeism despite poorly controlled cholesterol levels [20].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the 671 subjects included 656 who accepted drug treatment (DT group) in part I of this study [10], and 15 who had taken cholesterol-lowering drugs before this study and were not included in part I. Out of 671 subjects, 31 subjects were excluded because 25 had no follow-up data (rejected participation in this part II study), and 6 had no information about compliance.…”
Section: Compliance With Drug Treatmentmentioning
confidence: 99%
“…We therefore conducted a prospective study. The profiles of participants were described in detail in part I of this study 10). Briefly, we recommended a treatment with simvastatin, an HMG-CoA reductase inhibitor, in addition to a diet-based treatment program, for all eligible workers, with hypercholesterolemia diagnosed in a legally required medical check-up, and who had not been improved after a 3-month diet therapy.…”
mentioning
confidence: 99%
“…Yamaoka et al evaluated adherence to a α-glucosidase inhibitor on a four-grade scale ("take all as instructed," "usually take," "sometimes take," and "don't take") and demonstrated that adherence was lower than with other oral antidiabetic agents [24]. Tatemichi et al demonstrated that adherence improved according to the instructtions given by physician in an evaluation of long-term adherence in male Japanese workers using a four-grade scale (always took the drug according to the prescription (complete), occasionally forgot to take the drug (good), frequently forgot to take the drug (poor), always forgot to take the drug (very poor)) [25]. Evaluating adherence on a four-grade scale for forgetting to take medication or having left-over medication ("happens a lot," "sometimes happens," "doesn't happen very often," "almost never happens"), Kamei et al identified occupation and having diabetes as factors affecting adherence [26].…”
Section: Introductionmentioning
confidence: 99%